4(2w+3)+2(3+w)=

Simple and best practice solution for 4(2w+3)+2(3+w)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2w+3)+2(3+w)= equation:


Simplifying
4(2w + 3) + 2(3 + w) = 0

Reorder the terms:
4(3 + 2w) + 2(3 + w) = 0
(3 * 4 + 2w * 4) + 2(3 + w) = 0
(12 + 8w) + 2(3 + w) = 0
12 + 8w + (3 * 2 + w * 2) = 0
12 + 8w + (6 + 2w) = 0

Reorder the terms:
12 + 6 + 8w + 2w = 0

Combine like terms: 12 + 6 = 18
18 + 8w + 2w = 0

Combine like terms: 8w + 2w = 10w
18 + 10w = 0

Solving
18 + 10w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 10w = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 10w = 0 + -18
10w = 0 + -18

Combine like terms: 0 + -18 = -18
10w = -18

Divide each side by '10'.
w = -1.8

Simplifying
w = -1.8

See similar equations:

| 4(w-6)=3(a+1) | | 7x+13=2x+8 | | -21+7y=9x | | 58-2+7=8x | | 3a+34b= | | 0.1x=.2(2+x) | | 2(b+5)+6b=5b+2b+1 | | 4x-13x+10=0 | | -10h=-6(4+3h) | | .5xn=.333 | | 6x+2y=16.60 | | 4(5)-4x=4 | | -4k(k+6)-(9k-6)=-14k | | 3x+2.5x=60 | | P=2(1.08)t | | 4.9t^2+17.9t+5=0 | | 12.8*0.25= | | X-90=4x | | 5a=7+8a | | 4x-2(x-4)=-6+4x+10 | | (10x^2+30x)=(2x^2-30x-75) | | -2x+5(-2x-6)=18 | | 3-(6s-15)=4s+8 | | 20x^2+25x+75=0 | | 3x+3=x-18 | | -16=x-10 | | 24-6k=6(k-4) | | 0.4y+0.65x=60 | | 24-6k=6k(4-k) | | 6(1+4a)=-114 | | 3(9y+3)-9=2y+21 | | 39+0.75x=x |

Equations solver categories